Rhetorical Devices Used by Simon Sinek When Delivering an Inspirational Speech - Jonathan Calvin Candra; Esther Harijanti Kuntjara (Institute of Research and Community Outreach - Petra Christian University, 2022)
This study focuses on finding out the rhetorical devices used by Simon Sinek when delivering an inspirational speech and how they affect Simon Sinek’s inspirational speech. In this study, the writer used Harris’ (2018) theory of rhetorical question and Gregory’s (2018) theory of general purposes of speech to analyze the data. The writer employed a descriptive qualitative approach. The findings showed that Simon Sinek uses alliteration, parallelism, antithesis, and simile when delivering his speech. The missing device is metaphor because metaphor allows different interpretations, decreases the level of clarity in a speech. Each rhetorical devices affects the speech differently. Alliteration affects the speech using melody; parallelism with repetition and rhythm; antithesis with contrast, complexity, balance, and emphasis; and simile with vivid image, sense of familiarity, and clarity. Ultimately, rhetorical devices affect the inspirational speech in a positive way as they help amplify the meaning of the speech.